A representação da informação em prontuários de pacientes de hospitais universitários: uma análise à luz da teoria comunicativa da terminologia - Silva, Josiane Cristina da [UNESP] (2010)
Information Science develops methodologies for processing, accessing and transferring information and knowledge, in view of the needs and demands of users and establish relations with the Terminology, because when considering the function of organizing information and knowledge, both fulfill the role of retrieving and disseminating information and serve users in their informational needs. It is also noteworthy that, among the many possibilities of interdisciplinary studies in the field of Information Science, information in health care is of great importance. Although information has a core value in contemporary society, in health, scientific-technical information is vital. In this work, information in health care refers to the study of health care terminology, pointing out that the technical and scientific terms in this field are mainly used for reporting information and transferring of knowledge among professionals. However, the variation in the terminology of health care requires technical and scientific terms harmonized, since they show a lot of imprecision and ambiguity and can hinder the retrieval of information by health care professionals. Taking into consideration the need to use a more harmonious terminology, for better communication among health care professionals, emerged the proposal to highlight the importance of the Communicative Theory of Terminology through an analysis of the representation of information in medical records of patients from university hospitals, specifically in the Neurology field. It was observed in the comparison made among University Hospitals, namely, the Clinical Hospital at the Faculty of Medicine of Marília and the Clinical Hospital at the Faculty of Medicine of Ribeirao Preto, University of Sao Paulo that there are more similarities than differences at filling out patient records. As to the... (Complete abstract click electronic access below)